Structure-activity relationship studies on the macrolide exotoxin mycolactone of Mycobacterium ulcerans. - Nicole Scherr; Philipp Gersbach; Jean-Pierre Dangy; Claudio Bomio; Jun Li; Karl-Heinz Altmann; Gerd Pluschke (Public Library of Science (PLoS), 2013)
BACKGROUND: Mycolactones are a family of polyketide-derived macrolide exotoxins produced by Mycobacterium ulcerans, the causative agent of the chronic necrotizing skin disease Buruli ulcer. The toxin is synthesized by polyketide synthases encoded by the virulence plasmid pMUM. The apoptotic, necrotic and immunosuppressive properties of mycolactones play a central role in the pathogenesis of M. ulcerans. METHODOLOGY/PRINCIPAL FINDINGS: We have synthesized and tested a series of mycolactone derivatives to conduct structure-activity relationship studies. Flow cytometry, fluorescence microscopy and Alamar Blue-based metabolic assays were used to assess activities of mycolactones on the murine L929 fibroblast cell line. Modifications of the C-linked upper side chain (comprising C12-C20) caused less pronounced changes in cytotoxicity than modifications in the lower C5-O-linked polyunsaturated acyl side chain. A derivative with a truncated lower side chain was unique in having strong inhibitory effects on fibroblast metabolism and cell proliferation at non-cytotoxic concentrations. We also tested whether mycolactones have antimicrobial activity and found no activity against representatives of Gram-positive (Streptococcus pneumoniae) or Gram-negative bacteria (Neisseria meningitis and Escherichia coli), the fungus Saccharomyces cerevisae or the amoeba Dictyostelium discoideum. CONCLUSION: Highly defined synthetic compounds allowed to unambiguously compare biological activities of mycolactones expressed by different M. ulcerans lineages and may help identifying target structures and triggering pathways.